BEYOND THE SCREEN: AN EXPLORATION OF SOCIAL, INTELLECTUAL, AND COGNITIVE CHANGES AMONG CHILDREN IN THE DIGITAL AGE - PURVI SAMIRKUMAR SHAH, DR. DIPAKBHAI K MAKWANA (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
The present research paper looks at how daily screen duration or usage is impacting different development domains, levels like intellectual, social, physical and cognitive development of children. The primary data was collected through a structured household survey in Vadodara city, Gujarat. The study included 509 children from a total of 450 household samples undertaken during the study. The study adopted combined research methods where chi-square tests, ANOVA, OLS regression & correlation analysis tools were used to achieve the objective of i) exploring the relationships, ii) Impact of screen duration on developmental domains, iii) Gender based differences iv) Effect size. The results indicate to positive relationship between screen duration and the negative developmental impact on children. The average daily usage in hours is lowest found in the joint families with an average 2.5 hours duration of screen, which 71 percent observed to negative impact of children, while the highest average screen duration is found by 5 hours daily in SPN-single parents Nuclear family as the highest negative screen impact rate of 79 percent on children. Here, more time on screens was linked to higher negative outcomes across all domains, with the intellectual domain showing the strongest effect (Cramér’s V = 0.639). The analysis revealed extremely statistically significant associations (p < 0.0000001) between higher screen time and negative outcomes in all developmental domains. The strength of these associations, measured by Cramér's V, was found to be strong, ranging from 0.402 (Cognitive) to 0.639 (Intellectual). A clear dose-response relationship was identified, with the regression model indicating that for each additional hour of daily screen time, positive developmental outcomes decrease by approximately 2.94%. Furthermore, the effects were found to be gender-neutral. The intellectual domain was the most severely impacted, with over 72% of children in high-screen-time groups showing negative effects.